Heritigization and foreign diplomacy: Claiming a religious building to enhance Swedish-Russian contacts in the aftermath of the Cold War - Gunner, Gunilla; Nordbäck, Carola (Approaching Religion, 2023)
The article investigates the complex negotiation process regarding the renovation of St Catherine’s church in St Petersburg. Additionally, the goal is to gain novel understanding of how former religious spaces can be transformed and highlight the various significances these structures may possess in different contexts, particularly at the junction of religion and cultural heritage. Built in 1865, the church served as a place of worship for the Swedish-speaking congregation for nearly eighty years before being repurposed as a sports school. Recently, Sweden has aimed to restore the church and utilize it as a centre for Swedish–Russian relations. The article examines the reasons and arguments for renovation, as well as the progress that has been made to date. Additionally, it explores the role of Sweden in Russia through the perspectives of various stakeholders, including members of the congregation, diplomats, politicians, architects and priests.